Krisis Integritas Pemilu: Analisis Dirty Vote dalam Perspektif Politik Islam - Januari Riki Efendi; Hasan Bakti Nasution; Mardian Idris Harahap (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the integrity crisis of Indonesia's 2024 General Election as portrayed in the documentary film Dirty Vote through the classical Islamic political thought of Abu al-Hasan al-Mawardi and Imam Abu Hamid al-Ghazali. The study employs a qualitative multi-method design by combining Critical Discourse Analysis (CDA) of the documentary's empirical claims with library research on major Islamic political texts, including Al-Ahkam as-Sulthaniyyah, Ihya Ulumuddin, and Nasihatul Mulk. The findings indicate that electoral engineering—including manipulation of candidacy age requirements, gerrymandering through Papua's regional expansion, bureaucratic mobilization, weakened oversight by the KPU and Bawaslu, and pork-barrel politics through the politicization of social assistance—constitutes structured, systematic, and massive violations. From Al-Mawardi's perspective, these practices breach the social contract (bay'ah), misuse public funds (Baitul Mal), and produce a moral defect in leadership (Al-Jarh fi al-Adalah). Al-Ghazali's perspective interprets them as political moral decay (fasad al-siyasah), reinforced by the separation of religion from politics, exploitation of poverty (al-faqr), and declining intellectual integrity among opportunistic scholars (ulama al-su') within oversight institutions. The study proposes electoral reconstruction based on institutional accountability (amanah), regulatory transparency (shiddiq), impartial law enforcement ('adl), and the institutionalization of independent civil-society oversight as public control (hisbah).